Stimulasi Bagi Anak Yang Mengalami Keterlambatan Mandiri (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Children experiencing delayed independence face academic challenges that require targeted interventions. This article conducts a literature review to find effective stimulation methods for children with such delays. Through the literature review, effective strategies such as personalized interventions, early identification of challenges, and the supportive role of the environment are identified. This research emphasizes the importance of implementing targeted stimulation techniques for children with delayed independence, providing valuable insights for educators, caregivers, and practitioners by emphasizing personalized approaches and early intervention for maximum developmental outcomes.